Experiencing Physical Disability: Young African Women in Lesotho - Rafoneke, Seithati; Coetzee, Jan K.; Bülow, Pia H.; Jaffray, Penny; Young-Hauser, Amanda (Qualitative Sociology Review, 2019)
The article unwraps notions related to young African women’s lifeworld experiences of physical disability. The study is positioned in the broad context of the theoretical frameworks of phenomenology, existential sociology, the social construction of reality, feminist disability theory, and intersectionality. Focus is given to the way social systems of cultural oppression and discrimination impact women with physical impairments and manifest in how they perceive and make meaning of their everyday life experiences. Women with physical impairments often experience a double measure of oppression—being both female and disabled. When these women try to engage in a normal life and interact with others, they experience barriers imposed on them by their social reality—particularly in the form of cultural norms and patriarchal ideals. There are also instances where participants demonstrate resilience in the face of negative social stereotyping, instances that clearly show that they are not different, and do not perceive themselves as being different to able-bodied women. Drawing on semi-structured in-depth interviews with eight young Black women who are living with physical disabilities in Lesotho, the objective of this article is to examine their everyday life experiences within a predominantly able-bodied society.